2006
DOI: 10.1016/s1472-6483(10)60621-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an oral contraceptive pill on follicular development in IVF/ICSI patients receiving a GnRH antagonist: a randomized study

Abstract: This randomized controlled study compared the effectiveness of a gonadotrophin releasing hormone (GnRH) antagonist protocol with or without oral contraceptive (OC) pretreatment on the number of oocytes retrieved in IVF or intracytoplasmic sperm injection (ICSI) patients. Sixty-four patients were randomized to start recombinant human FSH (r-hFSH) on day 2 or 3 after OC withdrawal (OC group) or on day 2 of a natural cycle (control group). From stimulation day 6 onwards, all patients were treated with daily (0.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 32 publications
5
32
0
1
Order By: Relevance
“…There is limited body of data in the literature on the use OCP pretreatment prior to GnRH antagonist protocol including three prospective randomized studies [8][9][10]. However, these studies focus only on the young IVF population and include relatively small numbers of patients and cycles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is limited body of data in the literature on the use OCP pretreatment prior to GnRH antagonist protocol including three prospective randomized studies [8][9][10]. However, these studies focus only on the young IVF population and include relatively small numbers of patients and cycles.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this limitation in the GnRH antagonist protocol, patients can be offered the use of pretreatment with oral contraceptive pills (OCP) [4][5][6][7]. Moreover, a previous study has shown that OCP pretreatment before GnRH antagonist led to higher numbers of oocytes retrieved compared to the standard GnRH antagonist protocol [8]. On the other hand, longer stimulation periods and increased consumption of recombinant FSH (rFSH) were needed for stimulation [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effects of OCs or progestins pretreatment on outcome of IVF cycle remain inconclusive (Smulders et al, 2010), especially in PCOS which was often an exclusion criterion in many previous randomized trials investigating such effects (Cedrin-Durnerin et al, 2007;Huirne et al, 2006;Kolibianakis et al, 2006;Rombauts et al, 2006). OCs used for cycle scheduling in women with regular menses were suggested to have a remnant adverse effect on outcomes after fresh embryo transfer (Griesinger et al, 2010;Smulders et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a retrospective study of women with polycystic ovary syndrome (vs. normal controls) undergoing IVF treatment also found that the use of successive OCP (≥3 months) improved serum hormone levels, antral follicle counts, and implantation and pregnancy rates [12]. The use of OCP pretreatment has also been associated with a reduction in endometrial thickness compared with no pretreatment, possibly due to the sustained suppression of luteinizing hormone (LH) and estradiol at the start of stimulation [13,14]. Although several studies have suggested a positive association between pregnancy rate and greater endometrial thickness on the day of ovulation trigger, up to a maximum of 12 to 14 mm [15], a reduced endometrial thickness at the start of the cycle may be beneficial in some patients to avoid overly thick endometrium following ovarian stimulation with human menopausal gonadotropin (hMG) [16].…”
Section: Introductionmentioning
confidence: 99%